Modeling of thermal behavior and microstructure evolution during laser cladding of AlSi10Mg alloys. (March 2020) - Liu, Chuanming; Li, Chonggui; Zhang, Zhe; Sun, Shuai; Zeng, Ming; Wang, Feifei; Guo, Yajun; Wang, Jinqian
Highlights: An improved three-dimensional FEM is developed to simulate the cladding process. A temperature selection judgment mechanism is established for the simulation. The predicted geometry of the cladding layers agrees with the experiment results. Relationship between temperature gradient G and solidification rate R is found. Abstract: An improved three-dimensional finite element model has been proposed for studying the thermal behavior and microstructure evolution during laser cladding of AlSi10Mg alloys. Different material properties between AlSi10Mg powders and AlSi10Mg alloys are distinguished from the experiment and theoretical calculation to provide more reliable material parameters for simulation. In order to investigate the melting and solidification process during the formation of cladding layers, a temperature selection judgment mechanism is established to simulate the evolution of AlSi10Mg powders from the powder state to melting state and alloy state. In addition, to simulate the complex thermal behavior associated with powder particles and the voids between particles, a simplified exponential attenuation model is used for correcting the heat source. A complex asymmetric heat source considering about the different material properties and laser absorptivity on both sides of the remelting zone is used for multi-track cladding process. By simulating the temperature distribution of molten pool, the improved FEM could be used to predict the geometric shape of cladding layers (ignoring the effect of melting flow) and the temperature history. The simulation results show that the heat tends to diffuse to the unmelted powder owing to the asymmetric heat source during multi-track cladding, which leads to the asymmetry of cladding layers along the width direction. Based on the results of the temperature field simulations and the solidification characteristics of AlSi10Mg powders, the temperature gradient (G), solidification growth rate (R), cooling rate (G*R) and G/R are investigated to predict the morphology and size of the solidification microstructure under different laser scanning parameters. The scanning speed mainly determines the cooling rate during the laser cladding process, which results in different microstructures. Higher scanning speed leads to higher cooling rate, corresponding to a finer microstructure. Coarse dendrites are generated at the bottom of the molten pool, while finer dendrites are formed at the top.